EFL Students’ Awareness on Digital Literacy - Mardiah Mardiah; John Pahamzah; Akhmad Baihaqi (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2021)
This present research focuses on senior high school student’s awareness on digital literacy. The purpose of this study is to analyze how students are aware of accessing and managing digital information. The method of the research used case study. Data collecting techniques used observation, questionnaire, and interview. Regarding the research location, the researchers involved SMA Negeri 1 Serang as the locus of the research. This involved thirty students as respondents to collect data from questionnaires, and two teachers for interviews. The result of the questionnaires show that the type of digital literacy tools recommended forstudentsin building their digital literacy awareness cover Accessing, Managing, Evaluating, Integrating, and Creating tools and programs.The result of the interview and observation, furthermore, show thatall teachers and students can develop both learning materialand learning atmosphere using ICT; allstudents also have the ability to use digital tools for finding the information and references to support their learning processes.